The 2007 ESO Instrument Calibration Workshop : proceedings of the ESO workshop held in Garching, Germany, 23-26 January 2007 - Kaufer, A. (Springer, 2017)
The 2007 ESO Instrument Calibration workshop brought together more than 120 participants with the objective to a) foster the sharing of information, experience and techniques between observers, instrument developers and instrument operation teams, b) review the actual precision and limitations of the applied instrument calibration plans, and c) collect the current and future requirements by the ESO users. These present proceedings include the majority of the workshop's contributions and document the status quo of instrument calibration at ESO in large detail. Topics covered are: Optical Spectro-Imagers, Optical Multi-Object Spectrographs, NIR and MIR Spectro-Imagers, High-Resolution Spectrographs, Integral Field Spectrographs, Adaptive Optics Instruments, Polarimetric Instruments, Wide Field Imagers, Interferometric Instruments as well as other crucial aspects such as data flow, quality control, data reduction software and atmospheric effects.It was stated in the workshop that "e;calibration is a life-long learning process"e;'. In this sense, this book will be a reference point for all future efforts to improve instrument calibration procedures in astronomy.